Low Frequency of Fruit and Vegetable Consumption Among Canadian Youth: Findings From the 2012/2013 Youth Smoking Survey. (February 2016) - Minaker, Leia; Hammond, David
ABSTRACT: BACKGROUND: Frequent fruit and vegetable (FV) consumption is protective against some cancers, cardiovascular disease, and other chronic diseases. This study explores self‐reported frequency of FV consumption in a nationally generalizable sample of Canadian youth in grades 6‐12. METHODS: Data from grades 6‐12 students who participated in the 2012‐2013 Youth Smoking Survey (N = 47, 203) were used to examine frequency of FV consumption. Logistic regression models were fitted to examine differences in meeting national FV intake recommendations by sociodemographic, student, and regional characteristics. RESULTS: Approximately 10% of Canadian grade 6‐12 students met FV recommendations. Students in grades 6 and 7 had significantly higher odds of meeting recommendations relative to students in grades 8‐12. Students who reported achieving "mostly As" on their report cards had significantly higher odds of meeting FV recommendations relative to those receiving As and Bs, Bs and Cs, or Cs (OR = 0.71, OR = 0.53, and OR = 0.46, respectively, p < .0001 for each). Students in British Columbia and Ontario had higher odds of meeting recommendations relative to students in Newfoundland, Prince Edward Island, and Nova Scotia. CONCLUSIONS: Only 1 in 10 Canadian youth are meeting FV recommendations. Programs and policies to encourage FV consumption are required to help mitigate future health issues associated with inadequate FV consumption.